Onset of action of loratadine/montelukast in seasonal allergic rhinitis patients exposed to grass pollen - Friedrich, Horak; Petra, Zieglmayer; René, Zieglmayer; Patrick, Lemell (Arzneimittelforschung, 2010)
Given the impact of allergic rhinitis (AR) on quality of life, it is important that AR medications have rapid onset of symptom relief. The objective of this study was to determine the onset of action of lorata-dine (CAS 79794-75-5)/montelukast (CAS 151767-02-1) 10 mg/10 mg (L/M) versus placebo in seasonal AR (SAR) subjects. In this single-center, double-blind, crossover study, subjects with SAR and confirmed sensitivity to grass pollen received single doses of L/M or placebo following exposure to grass pollen in the Vienna Challenge Chamber. Subjects recorded symptoms at 15-min intervals during the first 2 h post dose and at 30-min interval during the next 2 h. After a 14-day washout, the subjects crossed over to the other treatment. The primary endpoint was onset of action of L/M, defined as the first time point at which the mean change from baseline in total symptom score became and remained significantly different with L/M versus placebo. Secondary end-points included nasal congestion score and rhinomanometry findings. Onset of action with L/M for total symptom score was 1 h, 45 min (P < 0.01 vs placebo). Significant improvements in subject-assessed nasal congestion scores (P < 0.01) and rhinomanometry (P = 0.036) were noted with L/M as compared with placebo. Overall, L/M was well tolerated. In conclusion, L/M demonstrated rapid onset for broad symptom relief, including nasal congestion, in subjects with SAR
Keywords: Allergic rhinitis; CAS 79794-75-5; CAS 151767-02-1; Loratadine; Montelukast; Nasal congestion; Vienna Challenge Chamber